Efeitos da inclinação da esteira na marcha de crianças com Síndrome de Down - Moura, Thayse de Lucena e (2009)
Background: Down syndrome (DS) is a genetic alteration characterized by being a nonprogressive congenital encephalopathy. Children with DS have hypotonia and developmental delays that interfere in the movement`s acquisition for these children. Objective: Analyze the effects of treadmill inclination on angle and spatiotemporal gait characteristics of these individuals. Methodology: We studied 23 subjects of both sexes, with ages ranged between 05 and 11 years, they presented ability to walk on level 5 classified according to the Functional Ambulation Category (FAC). Initially held a subjective evaluation of balance through a questionnaire (Berg Balance Scale-BBS) then the kinematic gait analysis was realized on a treadmill first, without inclination and then, with inclination of 10%, using the motion system analysis Qualisys System. Data analysis was done using BioStat 5.0 attributing significance level of 5%. Normality of data was verified using D'Agostino test and later was applied paired t-test to compare data in two experimental conditions. Results: There was a statistically significant difference in the spatiotemporal variables: reduction in the cadence (from 108.92 ± 39.07 to 99.11 ± 27.51, p <0.04), increase in cycle time (from 1.24 ± 0.27 to 1.36 ± 0.34, p = 0.03 ) and increase in time to take stock (from 0.77 ± 0.15 to 0.82 ± 0.18, p <0.001). Angular variables that showed statistically significant increasing were: the hip in the initial contact (12.23 ± 4.63 to 18.49 ± 5.17, p <0.0001) and max. flexion in balance (12.96±4:32 to 19.50 ± 4.51, p <0.0001 ), knee in the initial contact (15.59 to ± 6.71 to 21.63 ± 6.48, p <0.0001), the ankle in the initial contact (-2.79 ± 9.8 to 2.25 ± 8.79, p <0.0001), max dorsiflexion in stance (4.41 ± 10.07 to 7.13 ± 11.58, p <0.0009), maximum plantar flexion in the pre-assessment of the ankle joint (increase of -6.33 ± 8.77 to -2.69 ± 8.62, p <0.0004).Conclusions: The inclination acts in a positive way for angular and spatiotemporal features gait of children with Down syndrome, demonstrating possible benefit of using this surface in the gait rehabilitation of children with Down Syndrome